PUBLISITAS MELALUI PAMERAN TERHADAP TINGKAP PENJUALAN SEPEDA MOTOR KASUS PADA SEPADA MOTOR KAWASAKI PT. GREENTECH CAKRAWALA MOTORINDO PEKANBARU - Joko Mei Rianto; Meizy Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research is: (1) to find out and analyse the Exhibition was carried out and (2) to determine the influence of the exhibition on the level of sales of Motorcycles made by PT. Greentech Cakrawala Motorindo Pekanbaru. This research was conducted in the offices of Kawasaki PT. Greentech Cakrawala Motorido Pekanbaru Soweto where obtaining data that is located on jalan Soekarno-Hatta No. 1.2.3 Pekanbaru. The research method used was quantitative. With the object of research is the PT. Greentech Cakrawala Motorido Pekanbaru . With the method of data collection by means of Quisioner and interviews. Data analysis techniques using Simple Linear regression analysis. With the results of the research there is Publicity through Exhibits of the level of sales of Motorcycles Kawasaki PT. Greentech Cakrawala Motorindo Pekanbaru of 0.575Keywords: Promotion, Publicity, Exhibitions, Sales Levels